KETENTUAN UMUM DAN TATA CARA PERPAJAKAN: IMPLEMENTASI SELF ASSESSMENT SYSTEM DALAM MENINGKATKAN KEPATUHAN WAJIB PAJAK DI INDONESIA - Adik Tya Hasibuan; Nurul Syafriani, Ratih Silviany (CV. ADIBA AISHA AMIRA, 2024)
This research is intended to examine the practice of self-assessment systems in increasing taxpayer compliance in Indonesia. This research was conducted through a literature study method, where data was collected through theoretical analysis related to the research topic. The self-assessment system allows taxpayers to calculate, report and submit the taxes they should pay. It is hoped that this research can reveal in more depth how this system functions to improve tax compliance in Indonesia. The existence of this system not only helps increase tax revenues and administrative efficiency, but also encourages transparency, accountability and modernization of the tax system. By continuing to innovate and adapt policies according to technological developments and economic conditions, the implementation of the self- assessment system can be more optimal and sustainable